Numerical modeling of detection in contacts of a bismuth-antimony alloy with different materials - Cherner, Iacov (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2013)
Diode detectors (DDs) are widely used in electronic information and communication systems. In this paper, the numerical modeling of the electrical potential distribution and current passing in the contacts of a normal metal or a superconductor with a bismuth-antimony (Bi-Sb) semiconductor alloy are conducted. The possibilities to create DDs based on these contacts and working at the liquid helium temperature of 4.2 K or below are explored. The dependences of current responsivity (CR), voltage responsivity (VR), and noise equivalent power (NEP) on signal frequency (f) are analyzed. The role of the contact area is discussed. The obtained results are compared with literature data. DDs working at both the liquid nitrogen temperature (T = 77.4 K) and the liquid helium temperature are considered. The comparison with the available literature data shows that the proposed DDs can be 10-100 times better. The physical reasons of these advantages are discussed. It is shown that unique properties of Bi-Sb alloys and especially of a Bi0.88Sb0.12 alloy make these alloys promising materials for cryoelectronics.